Evaluation of Potential Function of Core-Shell Model for PbTiO3 Ferroelectric Material and Its Application for Polarization Calculation - Tran, The Quang; Nguyen, Van Hoi; Nguyen, Hoang Linh; Vuong, Van Thanh; Do, Van Truong (JST: Engineering And Technology For Sustainable Development, 2021)
In this study, the core-shell model is used to calculate the electric polarization for PbTiO3 ferroelectric material, in which, the interaction potential functions among atoms are determined by the fitting method based on the results from the first principle calculation. The investigations obtained show that the remnant polarization increases under tension and decreases under compression. The remnant polarization decreases with increasing the temperature. The phase transition from the ferroelectric phase to the paraelectric phase is determined at 605K and can occur at lower temperatures of 0K, 300K, 400K, 500K if the compression strain are 8%, 6%, 5%, 2%, corresponding. The hysteresis loop shrinks as the temperature increases and degrades into a curve at the temperature of 605K.